2020
DOI: 10.1016/j.drugalcdep.2020.107842
|View full text |Cite
|
Sign up to set email alerts
|

Smile judgment in substance use disorders and its relationship to interpersonal and emotional functioning: An eye-tracking investigation

Abstract: The current study explored the judgments individuals with Substance Use Disorders (SUDs) make regarding the authenticity of enjoyment smile expressions and masking smile expressions containing traces of negative emotions. Accuracy at identifying the masked negative emotions were also examined. Eye-movements were recorded to observe relationships between attentional processes and smile judgment. Additionally, the relationship between smile judgment, emotion dysregulation, and interpersonal problems were also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 82 publications
(164 reference statements)
8
8
0
Order By: Relevance
“…However, identifying which negative emotion was being masked by the smiles proved to be a more difficult task, as shown from modest accuracy rates (between 20 and 50% accuracy). This has been the case with other studies of authenticity judgment and recognition of negative emotions in masking smile expressions as well (e.g., [ 23 , 40 ].…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…However, identifying which negative emotion was being masked by the smiles proved to be a more difficult task, as shown from modest accuracy rates (between 20 and 50% accuracy). This has been the case with other studies of authenticity judgment and recognition of negative emotions in masking smile expressions as well (e.g., [ 23 , 40 ].…”
Section: Introductionsupporting
confidence: 70%
“…Further, we attempted to predict accuracy in smile authenticity judgment and recognition of negative emotions in masking smile expressions with each emotion ability variable (as in its own model and as a whole model) and examined relationships between accuracy at the judgment and recognition tasks and each emotion ability. The same judgment and recognition tasks used in Perron et al [ 42 ] and Pelot et al [ 40 ] were employed in the current study, except for measuring eye movements as they found that it was not a reliable indicator of task performance. As mentioned previously, emotional intelligence, emotional contagion, and emotional regulation have each been implicated in some way in our perception and recognition of emotions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 14 failed to meet inclusion criteria [ 16 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]; reasons for study exclusion can be found in Supporting information, Table S1.1 . We were left with 22 studies to be included for the primary analysis [ 17 , 27 , 33 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. A summary of the systematic review search process is shown in Figure 1 (PRISMA flow‐chart).…”
Section: Resultsmentioning
confidence: 99%